2019
DOI: 10.1016/j.ijnss.2019.06.010
|View full text |Cite|
|
Sign up to set email alerts
|

The Indonesian version of the Premature Infant Pain Profile–Revised: Translation and adaptation of a neonatal pain assessment

Abstract: PurposePain assessment is a key component of good pain management in hospitalized infants. This study aimed to translate and adapt a version of pain measurement in infants, the Premature Infant Pain Profile Revised (PIPP-R) into Indonesian.MethodThe adaptation process of the measuring instrument used a modified Brislin method which included forward translation, back translation 1, group discussion 1, back translation 2, group discussion 2, and pilot testing on neonatal nurses: feasibility test, inter-rater rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Destaca-se, ainda, que as consequências das condições de vidas à dor e ao estresse em neonatos, a curto e a longo prazo, ocasionam alterações na neurobiologia e no comportamento, consequentemente, afetam a deterioração da qualidade de vida. Portanto, é importante antecipar, prevenir e lidar com a dor e o estresse em neonatos, objetivando criar uma geração de alta qualidade no futuro (19) .…”
Section: Discussionunclassified
“…Destaca-se, ainda, que as consequências das condições de vidas à dor e ao estresse em neonatos, a curto e a longo prazo, ocasionam alterações na neurobiologia e no comportamento, consequentemente, afetam a deterioração da qualidade de vida. Portanto, é importante antecipar, prevenir e lidar com a dor e o estresse em neonatos, objetivando criar uma geração de alta qualidade no futuro (19) .…”
Section: Discussionunclassified
“…High correlations existed between PIPP and PIPP-R scores for both datasets (R 2 = 0.91 to 0.99). 8 The PIPP-R also has been demonstrated to have high cultural adaptation and has been successfully translated into languages such as Indonesian, 9 Nordic, 10 Portuguese, 11 and Turkish. 12 Research has demonstrated the psychometric properties of translated and adapted versions of the PIPP-R. [9][10][11][12] For example, high correlations were found between the Brazilian Portuguese versions of PIPP and PIPP-R scores for term and preterm infants undergoing heel lance and venipuncture (R 2 = 0.98) and receiving pain reducing strategies (ie, expressed breast milk, glucose, non-nutritive sucking, alone or combined) for procedural pain (R 2 = 0.96).…”
Section: The Premature Infant Pain Profile (Pipp) and The Premature I...mentioning
confidence: 99%
“…8 The PIPP-R also has been demonstrated to have high cultural adaptation and has been successfully translated into languages such as Indonesian, 9 Nordic, 10 Portuguese, 11 and Turkish. 12 Research has demonstrated the psychometric properties of translated and adapted versions of the PIPP-R. [9][10][11][12] For example, high correlations were found between the Brazilian Portuguese versions of PIPP and PIPP-R scores for term and preterm infants undergoing heel lance and venipuncture (R 2 = 0.98) and receiving pain reducing strategies (ie, expressed breast milk, glucose, non-nutritive sucking, alone or combined) for procedural pain (R 2 = 0.96). 11 The Indonesian version of the PIPP-R indicated high interrater reliability (intraclass correlation = 0.968, P = 0.001) and good internal consistency (α = 0.856) on a sample of 30 infants undergoing venipuncture for infusion or blood collection.…”
Section: The Premature Infant Pain Profile (Pipp) and The Premature I...mentioning
confidence: 99%
“…Em seguida, foi registrada a frequência cardíaca máxima e a saturação de oxigênio mínima acusada pelo monitor digital, além do estado de alerta basal. Durante o procedimento, o neonato foi observado por 30 segundos, utilizando-se os mesmos parâmetros já citados, somados ao tempo em que ele permaneceu com a testa franzida, olhos espremidos e sulco nasolabial acentuado (FITRI et al, 2019).…”
Section: Métodounclassified